2017
DOI: 10.1016/j.ijpddr.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

A novel in vitro image-based assay identifies new drug leads for giardiasis

Abstract: Giardia duodenalis is an intestinal parasite that causes giardiasis, a widespread human gastrointestinal disease. Treatment of giardiasis relies on a small arsenal of compounds that can suffer from limitations including side-effects, variable treatment efficacy and parasite drug resistance. Thus new anti-Giardia drug leads are required. The search for new compounds with anti-Giardia activity currently depends on assays that can be labour-intensive, expensive and restricted to measuring activity at a single tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“… 79 The efficacy of Malaria Box, a collection of 400 diverse compounds with antimalarial activity, as well as an other 1,600 known bioactive molecules, has been tested using an automated live-cell digital phase-contrast microscopy assay that permits automated assessment of Giardia growth without cell staining. 81 , 82 Other assays instead rely on transgenic Giardia parasites, based on either the assessment of glucuronidase activity in trophozoites 83 or the amount of luciferase bioluminescence in trophozoites and encysting parasites, the latest allowing bioluminescent monitoring of the drug efficacy in mouse infection model by imaging methods. 84 This last option is of paramount importance, since the increasing use of murine model of giardiasis is required for the pre-clinical evaluation of undesired pharmacokinetic/ pharmacodynamic properties.…”
Section: Introductionmentioning
confidence: 99%
“… 79 The efficacy of Malaria Box, a collection of 400 diverse compounds with antimalarial activity, as well as an other 1,600 known bioactive molecules, has been tested using an automated live-cell digital phase-contrast microscopy assay that permits automated assessment of Giardia growth without cell staining. 81 , 82 Other assays instead rely on transgenic Giardia parasites, based on either the assessment of glucuronidase activity in trophozoites 83 or the amount of luciferase bioluminescence in trophozoites and encysting parasites, the latest allowing bioluminescent monitoring of the drug efficacy in mouse infection model by imaging methods. 84 This last option is of paramount importance, since the increasing use of murine model of giardiasis is required for the pre-clinical evaluation of undesired pharmacokinetic/ pharmacodynamic properties.…”
Section: Introductionmentioning
confidence: 99%
“…The MMV Malaria Box molecules ( 4 ) have been extensively studied for their inhibitory potential against asexual and sexual stages of P. falciparum ( 24 ). This valuable antimalarial collection has also been screened against other parasitic species, such as kinetoplastids ( 19 21 ), helminths ( 17 ), Babesia ( 67 ), Theileria ( 68 ), Cryptosporidium ( 18 ), Toxoplasma ( 41 ), Giardia ( 69 ), and Entamoeba ( 41 ). These screens primarily focused on determining killing efficacies in whole-organism assays.…”
Section: Discussionmentioning
confidence: 99%
“…Comparative analysis showed that the luciferase-based assay described here has a high level of reliability and reproducibility based on the assay of a known standard drug, metronidazole, a previously-known alternative, albendazole, and determination of EC 50 s for selected hits from the Pathogen Box library. This assay overcomes the limitation of drug screening platforms that rely on assessment of parasite numbers without regard to parasite viability [ 27 , 28 ], since only viable parasite cells can produce the ATP required for the D-luciferin reaction.…”
Section: Discussionmentioning
confidence: 99%
“…Semi high-throughput assays using resazurin to measure cell viability [ 26 ] and another based on automated image analysis by cell stained-DAPI signal read-out have also been explored [ 27 ]. Most recently, a digital phase-contrast microscopy morphology-based assay method with enumeration by software was developed, which does not require cell staining [ 28 ]. The morphology-based assay is comparable to the previously reported DAPI stain method, but it relies solely on expensive software to identify and count parasites based on size and morphology [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation